Definition of priority tasks for agricultural development - Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Skliar, Radmila; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович (My University, 2020)
Innovative development of agriculture in Ukraine is based on the implementation of state agricultural and investment policy aimed at intensifying innovations as a priority component of the overall strategy of increasing national competitiveness, creating conditions for domestic agricultural enterprises to implement offensive strategy in foreign markets, support constructive competition in the domestic market. to stimulate agrarian formations to innovative activity, to ensure close integration of production and science, in order to promote the advanced development of scientific and technological sphere.
Keywords: agricultural; Innovative development